Targeting ERRs to counteract age-related muscle atrophy associated with physical inactivity: a pilot study - Bonanni, Roberto; Falvino, Angela; Matticari, Antonio; Rinaldi, Anna Maria; D’Arcangelo, Giovanna; Cifelli, Pierangelo; Iundusi, Riccardo; Gasbarra, Elena; Tancredi, Virginia; Cariati, Ida; Tarantino, Umberto (Frontiers in Physiology, 2025)
IntroductionEstrogen-related receptors has been suggested as a potential therapeutic target to counteract muscle decline associated with aging or inactivity, being known to regulate mitochondrial function and cellular respiration by up-regulating key factors in muscle responses to exercise. This study aimed to evaluate the targeting of ERRs in myoblasts isolated from the skeletal muscle of inactive women by assessing the metabolic and expression changes associated with its activation.MethodsTwenty women undergoing hip arthroplasty for coxarthrosis were enrolled and divided into an active group (n = 10) and an inactive group (n = 10) based on self-reported physical activity. During surgery, muscle biopsies were taken for histological and western blotting analysis, measuring the expression levels of NADPH oxidase 4 (NOX4), sirtuin 1 (SIRT1), peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α), estrogen related receptor alpha (ERRα), and fibronectin type III domain-containing protein 5 (FNDC5). Primary cultures of myoblasts were set up from the muscle tissue of inactive women and treated with the ERRs agonist, SLU-PP-332, for subsequent qualitative and quantitative investigations. In addition, myoblasts were differentiated into myotubes for 15 days, and the success of differentiation was evaluated by immunofluorescence analysis.ResultsClinical and instrumental evaluation showed less functional limitation, higher handgrip strength values, and significantly reduced visual analogue scale scores in active subjects, in association with a significant increase in muscle fiber diameter. In addition, significantly higher expression of NOX4, concomitant with reduced levels of SIRT1, PGC-1α, ERRα, and FNDC5, was detected in the muscle tissue of inactive women. Interestingly, SLU-PP-332 treatment promoted down-regulation of NOX4 and upregulation of SIRT1, PGC-1α, ERRα, FNDC5, Akt, and B-cell lymphoma 2 (Bcl-2) in myoblasts, reducing cytotoxicity, oxidative stress, and senescence, as well as increasing levels of reduced glutathione. Furthermore, SLU-PP-332 treatment promoted abundant myotube formation, positively influencing cell differentiation.DiscussionTargeting ERRs could represent a promising therapeutic strategy to counteract muscle atrophy in elderly and sedentary subjects. However, further studies are needed to clarify the molecular mechanisms involved and explore the impact of ERRs activation on muscle metabolism.